Review: Integrated Scientific Literacy on Natural Science Learning - Ninda Yera Setyo Nainggolan; Woro Sumarni; Wiyanto; Sutikno; Suharto Linuwih (JPP (Jurnal Pendidikan dan Pembelajaran), 2021)
This literature review reveals the journal publication on integrated scientific literacy in natural science learning. A systematic review was carried out through a modified and adopted items selected for the systematic review and meta-analysis (PRISMA). The articles with integrated scientific literacy have been detected in a number of journals, such as ERIC, SCIENCE DIRECT, IJSE, SE, JRST, IOP SCIENCE, DOAJ, and Springer, using the keywords of "Science Literacy teaching materials." The results suggest that the number of studies on integrating scientific literacy learning materials from 2016 to 2020 is still low, so that the opportunity for its development remains wide.